PERAN PENDIDIKAN KEWIRAUSAHAAN DAN PEMANFAATAN MEDIA SOSIAL TERHADAP PEMBENTUKAN JIWA WIRAUSAHA MAHASISWA DALAM MENGEMBANGKAN USAHA KECIL - Indra Prayogi Sianturi; Andreas Mian Asiniroha Pasaribu; Linda Sariana Hutahaean; Desi Peronika Putri Sagala; Patricia Herpayanti Rajagukguk; Nalom Siagian (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
Entrepreneurship education plays a strategic role in shaping students’ entrepreneurial spirit amid limited employment opportunities and the rapid development of the digital economy. In addition, social media utilization has become a relevant medium for students in developing small businesses. This article aims to analyze the role of entrepreneurship education and social media utilization in shaping students’ entrepreneurial spirit in developing small enterprises. This study employed a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation and analyzed using descriptive qualitative techniques. The findings indicate that entrepreneurship education contributes to the development of students’ entrepreneurial attitudes, mindset, and motivation, while social media serves as a practical medium for implementing entrepreneurial activities that support small business development. The integration of entrepreneurship education and social media utilization effectively fosters an adaptive and innovative entrepreneurial spirit among students. Therefore, entrepreneurship education and social media utilization should be continuously strengthened in higher education institutions.